2019
DOI: 10.1039/c9ra07793f
|View full text |Cite
|
Sign up to set email alerts
|

Nanoceria-modified platinum supported on hierarchical zeolites for selective alcohol oxidation

Abstract: Illustration of Pt/CeO2 supported on hierarchical zeolites promoting the highly selective oxidation of benzyl alcohol to benzaldehyde.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
(50 reference statements)
1
4
0
Order By: Relevance
“…On the other hand, the other samples, including Pt-K-Hie-ZSM5, Pt-Ca-Hie-ZSM5, and Pt-Ba-Hie-ZSM5, were exchanged with the MCl 2 solution (M = K, Ca, and Ba). Hence, even after the catalyst modification via the alkaline-exchange and Pt impregnation processes, the MFI framework and the high surface structure are maintained, exhibiting similar hierarchical ZSM-5 structures to the pristine hierarchical ZSM-5, which is also similar to what has been observed previously. ,,, …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, the other samples, including Pt-K-Hie-ZSM5, Pt-Ca-Hie-ZSM5, and Pt-Ba-Hie-ZSM5, were exchanged with the MCl 2 solution (M = K, Ca, and Ba). Hence, even after the catalyst modification via the alkaline-exchange and Pt impregnation processes, the MFI framework and the high surface structure are maintained, exhibiting similar hierarchical ZSM-5 structures to the pristine hierarchical ZSM-5, which is also similar to what has been observed previously. ,,, …”
Section: Resultssupporting
confidence: 84%
“…Hence, even after the catalyst modification via the alkaline-exchange and Pt impregnation processes, the MFI framework and the high surface structure are maintained, exhibiting similar hierarchical ZSM-5 structures to the pristine hierarchical ZSM-5, which is also similar to what has been observed previously. 41,42,57,66 To verify the alkaline ion and Pt compositions in all the prepared samples, the summarized XRF results are demonstrated in Table S2. It was found that Na was completely replaced by exchanged alkaline metals even using only a single cycle of the ion-exchange process at room temperature for 6 h. The mole percentage of the metal cation is approximately 0.01, 0.02, 0.01, and 0.01 for Na + , K + , Ca 2+ , and Ba 2+ , respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Thus, the electron transfer between ZSM-5 and CeO x and the associated oxygen vacancies may generate additional WAS or modify the electronic environment of Al sites, thereby increasing the population of WAS. Such atomically dispersed Ce species, which are usually multivalent (Ce δ+ ), , may facilitate the mobility of oxygen on the surface to promote H 2 O dissociation into new Al–OH species, acting as Lewis sites . Nevertheless, a high Ce δ+ /H + ratio (∼0.179) may block H + sites to bind NH 3 molecules (as evidenced by N 2 sorption data in Figure S4A,B), leading to a decrease in the population of SAS (Table ) and BAS (Figure B) .…”
Section: Resultsmentioning
confidence: 99%
“…As oxidation of alcohol to aldehyde and carboxylic acid is a very important reaction in organic as well as biochemistry, many catalytic systems have been developed with different reaction conditions and yields. [ 31–61 ] Despite several reports, the existing methodologies are often plagued by disadvantages like harsh reaction conditions, use of toxic metals, and poor recyclability. Photocatalysis emerged as an important tool to carry out such reaction in a more environmentally friendly condition without application of external heat.…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol oxidation by copper catalyst is a well-known process and extensively studied as reported in literature. [31][32][33][34][35][36][37][38][39] The oxidation process has been explored in various methodologies including traditional heating, [40][41][42][43][44] microwave irradiation, [39,[45][46][47] electrochemical method, [48][49][50][51][52] and ultrasonic irradiation. [53][54][55] Interestingly, though alcohol oxidation is reported by photocatalytic systems like Ag 2 S-CdS junction [56][57][58] and platinum nanocluster/graphitic carbon nitride, [59,60] however, use of copper complexes as photocatalyst remains rare and largely unexplored.…”
Section: Introductionmentioning
confidence: 99%